Dystocia due to dicephalus distomus monster in a crossbred Jersey cow - KHAN, M Z; ISLAM, R; WAR, B A (The Indian Journal of Animal Reproduction, 2007)
Relieving of dystocia due to Dicephalus distomus monster with forced extraction in a crossbred Jersey Cow is discussed.